Macrophage Folate Receptor-Targeted Antiretroviral Therapy Facilitates Drug Entry, Retention, Antiretroviral Activities and Biodistribution for Reduction of Human Immunodeficiency Virus Infections - Puligujja, Pavan (2013)
Macrophages serve as vehicles for the carriage and delivery of polymer-coated nanoformulated antiretroviral therapy (nanoART). Although superior to native drug, high drug concentrations are required for viral inhibition. Herein, folate-modified atazanavir/ritonavir (ATV/r)-encased polymers facilitated macrophage receptor targeting for optimizing drug dosing. Folate coating of nanoART ATV/r significantly enhanced cell uptake, retention and antiretroviral activities without altering cell viability. Enhanced retentions of folate-coated nanoART within recycling endosomes provided a stable subcellular drug depot. Importantly, five-fold enhanced plasma and tissue drug levels followed folate-coated formulation injection in mice. Folate polymer encased ATV/r improves nanoART pharmacokinetics bringing the technology one step closer to human use.